2021
DOI: 10.1109/jlt.2021.3080631
|View full text |Cite
|
Sign up to set email alerts
|

Power Over Fiber in C-RAN With Low Power Sleep Mode Remote Nodes Using SMF

Abstract: Power over fiber (PoF) with sleep mode operation in centralized radio access networks (C-RAN) of low power Remote Radio Heads (RRH) helps to reduce power consumption. This proposal includes bundles of single mode optical fibers (SMF) as part of the 5G C-RAN front-haul solution for providing control on power consumption by selectively activating some parts of the RRH. We experimentally demonstrate a PoF system based on 14.43 km of SMF feed by 2.24W giving 226 mW electrical power at the RRH for control, battery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 18 publications
(25 reference statements)
0
18
0
Order By: Relevance
“…In some cases, the same fiber transmits data at a specific wavelength and carries power using a different wavelength, which is generally called a share scenario, 23,24 which has a trade-off to meet the specifications of both applications simultaneously with a special attention to the high power laser 25 and the potential appearance of non-linear effects in the optical fiber. 26 Optical data systems use high quality lasers, which exhibit very narrow monochromatic and highly coherent emission. The laser wavelength must also correspond to the second or third communication windows of the optical fiber (centered at 1.3 and 1.55 mm, approximately, see Figure 2, top left), where attenuation and dispersion are very low, which is key because of the long distances covered by these links (hundred or thousand kilometers).…”
Section: Llmentioning
confidence: 99%
“…In some cases, the same fiber transmits data at a specific wavelength and carries power using a different wavelength, which is generally called a share scenario, 23,24 which has a trade-off to meet the specifications of both applications simultaneously with a special attention to the high power laser 25 and the potential appearance of non-linear effects in the optical fiber. 26 Optical data systems use high quality lasers, which exhibit very narrow monochromatic and highly coherent emission. The laser wavelength must also correspond to the second or third communication windows of the optical fiber (centered at 1.3 and 1.55 mm, approximately, see Figure 2, top left), where attenuation and dispersion are very low, which is key because of the long distances covered by these links (hundred or thousand kilometers).…”
Section: Llmentioning
confidence: 99%
“…In such RoF networks, the actual utilization of PWoF requires a power feeding capability of at least several tens of watts that can drive a small and medium-sized RAU without any external power supply systems. As an approach to drive RAUs without achieving sufficient power feeding capability, it has been reported that a battery can be deployed in the RAU in order to use "sleep mode" [23], [24] and to control the electric power supplied to RAUs [25]. However, when these systems are deployed in a larger number of RAUs, maintenance costs due to installment and replacement of batteries will become a significant issue.…”
Section: Pwof For Rof Networkmentioning
confidence: 99%
“…For example, SMFs can be used to transmit high-power optical signals to feed some parts of 5G-NR ARoF networks, e.g., low power Remote Radio Heads (RRHs) or Radio Frequency (RF) amplifiers therein [6]. This technique is called Power over Fiber (PoF), and has been integrated with RoF transmission in C-RAN based on SMFs [7,8], Multicore Fibers (MCF) [9,10,11], Multimode Fibers (MMF) [12,13], Double-Clad Fibers (DCF) [14], and in Plastic Optical Fiber (POF) for in homenetwork scenarios [15].…”
Section: Introductionmentioning
confidence: 99%